A Dynamic Hydro-Socio-Technical Policy Analysis of Transboundary Desalination Development - Page, Ashley; Langarudi, Saeed P.; Forster-Cox, Sue; Fernald, Alexander (Journal of Environmental Accounting and Management, 2026)
Global realities of water shortages and population growth – coupled with water quality concerns – increase tension over water allocation and jeopardize the sustainment of societies. Desalination of brackish water exists as an approach to augment inland freshwater supplies. Possible strain on freshwater supply in the transboundary Sunland Park-Santa Teresa-San Jerónimo-Anapra (SSSA) region, along the United States-Mexico border catalyzed interest in the prospect of desalination, but its effects here remain unknown. Hydrosociology literature recognizes the need to develop integrative water research methodology. No established criteria exist for these calls in the literature, and this approach has not yet been expanded as a hydrologic-social-technical (hydro-socio- technical) framework or applied to a policy case study examining desalination or transboundary water management. This study developed a system dynamics model to analyze the necessity and hydrologic impacts of desalination within SSSA’s complex hydro-socio-technical system. The study could not reject the hypothesis that desalination fails to represent necessary or hydrologically beneficial policy solutions for SSSA, as analyzed from this hydro-socio-technical systems perspective through at least the 100-year period. This research introduces the concept of perceived water availability as a means to recognize the correlation between water usage and the perception of available water. The results will inform emerging policy decision-making efforts in SSSA regarding the future of the community’s water supply and serve as a case study for communities facing similar water policy considerations.